A Low‐Concentration Electrolyte for High‐Voltage Lithium‐Metal Batteries: Fluorinated Solvation Shell and Low Salt Concentration Effect. Issue 52 (28th November 2022) - Deng, Rongyu; Chu, Fulu; Kwofie, Felix; Guan, Zengqiang; Chen, Jieshuangyang; Wu, Feixiang
Abstract: Concentration of electrolyte has significant effects on performances of rechargeable batteries. Previous studies mainly focused on concentrated electrolytes. So far, only several recipes on low‐concentration electrolytes were studied, performing enhanced performance in advanced rechargeable batteries. Here, based on common electrolyte components, a low‐concentration electrolyte composed of 0.2 M lithium hexafluorophosphate (LiPF6 ) solvated in fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) is employed for high‐voltage Li metal battery. The synergistic working mechanisms of introducing fluorine‐containing solvent in the solvated structure and low salt concentration effect are revealed, resulting in LiF‐rich, uniform, and robust solid electrolyte interphase layer and fewer unfavorable decomposition products. As a result, this low‐concentration electrolyte significantly enhances electrochemical performances of Li||Li symmetric cells and high‐voltage LiCoO2 ||Li batteries. Abstract : A low‐concentration electrolyte was employed in high‐voltage lithium metal batteries. The synergistic effects of fluorinated solvation shell and low salt concentration generated robust and LiF‐rich SEI and fewer unfavorable decomposition products. The excellent performance implies that the optimization of low concentration electrolytes is a successful solution for low‐cost and large‐scale electrolyte designs.